40-Hz Blue Light Changes Hippocampal Activation and Functional Connectivity Underlying Recognition Memory - Lin, Zhenglong; Hou, Gangqiang; Yao, Youli; Zhou, Zhifeng; Zhu, Feiqi; Liu, Linjing; Zeng, Lingwu; Yang, Yatao; Ma, Junxian (Frontiers in Human Neuroscience, 2021)
Research on light modulation has typically examined the wavelength, intensity, and exposure time of light, and measured rhythm, sleep, and cognitive ability to evaluate the regulatory effects of light variables on physiological functions. Gamma oscillations are particularly important for memory function, and recent studies indicate that these oscillations can be induced by 40 hertz (Hz) light stimuli, a phenomenon that may have potential clinical utility. As one of the main dimensions of light, few studies have attempted to manipulate the frequency of light to test the effect on the processing patterns of higher cognitive functions in a healthy brain. In the current study, we examined the effects of a one-hour exposure to either 40-Hz blue or 0-Hz light on brain activation and functional connectivity during a recognition memory task. Through joint augmentation of visual area activation, 40-Hz light enhanced brain areas mostly in the limbic system that are related to memory, such as the hippocampus and thalamus. Conversely, 0-Hz light enhanced brain areas mostly in the prefrontal cortex. Additionally, functional connection analysis, with the hippocampus as the seed point, showed that 40-Hz light enhanced connection with the superior parietal lobe while reducing the connection with the default network. These findings provide novel evidence that 40-Hz light can effectively regulate the recognition-related memory network. Differences in modulation of brain regions throughout the cognitive functional network, due to differences in light frequency, may also suggest that a better regulatory effect was achieved. Specifically, cognitive functions should be modulated using frequencies that are more sensitive or effective in the target brain regions and their corresponding functional networks.